Environmental policies, product market regulation and innovation in renewable energy - Lionel Nesta; Francesco Vona; Francesco Nicolli (Fondazione Eni Enrico Mattei (FEEM), 2012)
We investigate the effectiveness of policies in favor of innovation in renewable energy under different levels of competition. Using information regarding renewable energy policies, product market regulation and high-quality green patents for OECD countries since the late 1970s, we develop a pre-sample mean count-data econometric specification that also accounts for the endogeneity of policies. We find that renewable energy policies are significantly more effective in fostering green innovation in countries with deregulated energy markets. We also find that public support for renewable energy is crucial only in the generation of high-quality green patents, whereas competition enhances the generation of green patents irrespective of their quality.
Keywords: Q55; Q58; Q42; Q48; O34; 330; Renewable Energy Technology; Patents; Environmental Policies; Product Market Regulation; Policy Complementarity; Regenerative Energie; Förderung regenerativer Energien; Wirkungsanalyse; OECD-Staaten